Faktor-Faktor yang Berhubungan dengan Pemberian ASI Eksklusif Pada Ibu Primipara - Fidiawati, Reni; Sanjaya, Riona; Veronica, Septika Yani; Febriyanti, Hellen (Ners Akademika, 2022)
Purpose: The purpose of this study was to determine the factors associated with exclusive breastfeeding for primiparous mothers in the the working area of the UPTD. Puskesmas Bengkunat Belimbing In 2021. Research Methodology: The design of this research is descriptive non-experimental correlation, namely correlation research with cross sectional method. The population in this study were all primiparous mothers who had babies aged 7-12 months in the working area of UPTD. Puskemas Bengkunat Belimbing in 2021, totaling 52 primiparous mothers. A sample of 35 primiparous mothers was taken from the population using a probability sampling technique with random groups (cluster random sampling). Bivariate analysis in this study used the chi-square test with an alpha (?) value of 0.1. Result: The results showed that maternal knowledge (p-value of 0.009), education of primiparous mothers (p-value of 0.025), occupation of primiparous mothers (p-value of 0.046), maternal health of primiparous (p-value of 0.027), support of husband (p-value of 0.003), support for health workers (p-value of 0.771), family income (p-value of 0.001) and values ??and cultural customs (p-value of 0.001) have a corelations with exclusive breastfeeding to primiparous mothers.